2021
DOI: 10.1038/s41598-021-94236-y
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis for the structural dynamics of human mitochondrial chaperonin mHsp60

Abstract: Human mitochondrial chaperonin mHsp60 is essential for mitochondrial function by assisting folding of mitochondrial proteins. Unlike the double-ring bacterial GroEL, mHsp60 exists as a heptameric ring that is unstable and dissociates to subunits. The structural dynamics has been implicated for a unique mechanism of mHsp60. We purified active heptameric mHsp60, and determined a cryo-EM structure of mHsp60 heptamer at 3.4 Å. Of the three domains, the equatorial domains contribute most to the inter-subunit intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
(51 reference statements)
2
11
0
Order By: Relevance
“…In the presence of their own cochaperonins, chaperonins display decreased ATPase activities. For example, mHsp60 displays 50% decrease in the ATPase activity in the presence of mHsp10 ( 23 , 26 28 , also Fig. 2 C, Table 2 ).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In the presence of their own cochaperonins, chaperonins display decreased ATPase activities. For example, mHsp60 displays 50% decrease in the ATPase activity in the presence of mHsp10 ( 23 , 26 28 , also Fig. 2 C, Table 2 ).…”
Section: Resultsmentioning
confidence: 93%
“…Unlike the paradigm bacterial chaperonin GroEL, mHsp60 is intrinsically dynamic as evident by its irreversible dissociation to monomers 24 , 25 . In our recent structural analysis 23 , we found that mHsp60 contains unique sequences that weaken the inter-subunit interaction, accounting for dynamics of the subunit association. In this study, we found that the V72I mutation fortuitously fosters inter-subunit interactions including a potential charge-charge interaction between K74 and S44, stabilizing the subunit association.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations